The growth rate of S. aureus when treated with Azithromycin alone and combined with Syzygium cumini decoctation - Rio Risandiansyah; Yoni Rina Bintari (JIMR - Journal of Islamic Medicine Research, 2017)
ABSTRACTIntroductiom: Resistance to antibiotics is the result of adaptive and spontaneous mutations, which can be suppressed by use of combinatory antibiotics. Synergistic effects between certain plants in combination with antibiotics is known, yet the mutation frequency of such combinations is still unexplored. Therefore, this study aims to measure the spontaneous mutational frequency of S. aureus for Azithromycin (AZM) resistance alone and in combination with Syzygium cumini decocta (SCD), known for its antimutagenic effect. Method: This study uses fluctuation analysis with 39 replicate cultures in selective media using AZM alone, SCD alone, and AZM combined with SCD at 1x MIC and analysing resistant strains based on its log phase delay in liquid media in a 24-hour period. AZM and SCD showed antibiotic activity against S. aureus. Results: Time-point growth comparison showed two cultures in AZM selective medium with no delayed log phase between S. aureus in non-selective medium and absorbance >1.0 after 24 hours, indicating resistance to AZM. Conclusion: Increased growth suppression was observed in combination between AZM combined with SCD, compared to AZM and SCD alone. The spontaneous mutation frequency of S. aureus against AZM was 0.182, while both SCD and AZM combined with SCD had zero mutational events for antibiotic resistance.Keywords:Antibiotic Resistance, Combinatorial Antibiotic Therapy (CAT), Mutation frequency, Syzygium cumini.